Microskin Grafting for Vitiligo - Gupta, Devendra K.; SpringerLink (Online service) (London : Springer London, 2009)
Over the last two decades, various surgical therapies have been used in the treatment of stable refractory vitiligo, none of which are very popular due to their intrinsic drawbacks. The cellular graft technique are costly and required a good laboratory and infrastructure and the ultimate results are no better than tissue grafting technique except that these can cover a wide vitiliginous area. Thus no procedure can claim to be the gold standard and, consequently, there is always a need for the technique that gives best results without complications. Microskin Grafting For Vitiligo describes the technique of using small skin particles prepared from ultra thin or thin split thickness skin grafts in the effective treatment of vitiligo. The technique benefits from a good expansion ratio, e.g. small donor skin to treat a large vitiliginous area. The book$1 (Bs emphasis is on illustrating the concepts using numerous images and minimal text and thus enables a highly practical evaluation of the procedure. The book highlights that the technique is simple to learn and execute, cost effective, and can treat large areas in one operative session. Therefore, the book will be of interest to not only postgraduate students but also the clinical dermatologist, general practitioner and surgeon.s
Surgical Management -- Surgical Therapies -- Concept of the Stability of Vitiligo -- Classification of Surgical Treatment Modalities -- Excision with Primary Closure -- Thin and Ultra Thin Split Thickness Skin Grafts (STSG-UT, STSG-T) -- Split Thickness Skin Graft-Suction Blister Epidermis (STSG-BE) -- Full Thickness Skin Graft (FTSG) -- Cellular Grafts -- Microskin Grafting -- What Is a Microskin Graft? -- Preparation of Recipient Vitiliginous/Leukodermic Areas -- Superficial Dermabrasion of Vitiliginous Skin -- Donor Area Selection -- Skin Graft Harvesting -- Microskin Grafting Tools -- Techniques of Microskin Grafts Distribution on Ablated Vitiliginous Areas -- Step-by-Step Microskin Grafting Techniques -- Microskin Grafting by Direct Spread Method -- Microskin Grafting by Floatation Method -- Microskin Grafting by Spraying Method in Extensive Vitiligo Management -- Surgical Outcomes -- Complications Involved in Various Surgical Techniques -- Outcome of Various Techniques of Vitiligo Surgery.
Keywords: Medicine; Dermatology; Plastic surgery; Medicine & Public Health; Dermatology; Plastic Surgery; Electronic books